2020
DOI: 10.3390/molecules26010119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chemical Profiles of the Essential Oils from Different Varieties of Psidium guajava L.

Abstract: Guava (Psidium guajava) leaves are commonly used in the treatment of diseases. They are considered a waste product resulting from guava cultivation. The leaves are very rich in essential oils (EOs) and volatiles. This work represents the detailed comparative chemical profiles of EOs derived from the leaves of six guava varieties cultivated in Egypt, including Red Malaysian (RM), El-Qanater (EQ), White Indian (WI), Early (E), El-Sabahya El-Gedida (ESEG), and Red Indian (RI), cultivated on the same farm in Egypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 48 publications
0
17
1
1
Order By: Relevance
“…The Egyptian ecospecies of the present study yielded higher EO yield compared to Iranian [ 27 ] and Saudi [ 28 ] ecospecies, which had 0.20 and 0.21%, respectively. This variation in oil production could be ascribed to environmental, climatic, or genetic factors [ 5 , 6 , 29 , 30 , 31 ]. The term “ecospecies” means that species of the plant can be divided into several ecotypes (a genetically distinct population of plants that is growing in a particular habitat).…”
Section: Resultsmentioning
confidence: 99%
“…The Egyptian ecospecies of the present study yielded higher EO yield compared to Iranian [ 27 ] and Saudi [ 28 ] ecospecies, which had 0.20 and 0.21%, respectively. This variation in oil production could be ascribed to environmental, climatic, or genetic factors [ 5 , 6 , 29 , 30 , 31 ]. The term “ecospecies” means that species of the plant can be divided into several ecotypes (a genetically distinct population of plants that is growing in a particular habitat).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Al-Rowaily et al [ 51 ] and El-Amier and Al-hadithy [ 52 ] documented values on other wild species which are within the range of our study, but lower values were documented by Zahran and El-Amier [ 53 ]. The difference in composition could be attributed to the differences in origin, plant species, age, ecological, and climatic factors, or it can be correlated to the physiological status of the plant itself and nutrients available in the soil [ 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the chemical composition of EOA demonstrated the β‐caryophyllene (28.83%) and α‐Pinene (28%) as the major constituents (Chrystal et al., 2020; Savoldi et al., 2020; Soliman et al., 2016); while the chemical profile of the EOG reported β‐caryophyllene (26.6%), β‐bisabolol (19.5%), limonene (17.8%), and caryophyllene oxide (15.5%) as the major components (da Silva de Souza et al., 2017; Hassan et al., 2020; Mendes et al., 2017; Silva et al., 2019). Qualitative and quantitative variations of compounds in the same EOs are common since it is well established that chemotaxonomical differences, physiological age, harvesting seasons, plant parts, and/or extraction methods may affect the composition of EOs (Dhifi et al., 2016; Khadhri et al., 2014; Mohammadhosseini et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the biological activities of EOs are strongly associated with their chemical composition. Although the chemical profile of EO from araçá and guava leaves has already been investigated (Bermúdez‐Vásquez et al., 2019; Chrystal et al., 2020; Hassan et al., 2020; Savoldi et al., 2020; Silva et al., 2019), additional studies are necessary since the high variability of chemical constituents can be influenced by external and internal factors of the plant. This information is of great relevance for the valorization of regional raw materials with outstanding biological potential.…”
Section: Introductionmentioning
confidence: 99%